Uncoupling of endothelial nitric oxide synthase in cerebral vasculature of Tg2576 mice. (15th July 2015) - Santhanam, Anantha Vijay R.; d'Uscio, Livius V.; He, Tongrong; Das, Pritam; Younkin, Steven G.; Katusic, Zvonimir S.
Abstract: In this study, we tested the hypothesis that reduced bioavailability of tetrahydrobiopterin (BH4 ) is a major mechanism responsible for pathogenesis of endothelial dysfunction in cerebral microvessels of transgenic mice expressing the Swedish double mutation of human amyloid precursor protein (APP) (Tg2576 mice). Endothelial nitric oxide synthase (eNOS) protein expression was significantly increased in cerebral vasculature of Tg2576 mice. In contrast, bioavailability of BH4 was significantly reduced ( p  < 0.05). Moreover, superoxide anion production was increased in cerebral microvessels of Tg2576 mice ( p  < 0.05). Incubation with NOS inhibitor, N ω ‐nitro‐L‐arginine methyl ester, decreased superoxide anion indicating that uncoupled eNOS is most likely the source of superoxide anion. Increasing BH4 bioavailability either exogenously by BH4 supplementation or endogenously by treatment with the selective peroxisome proliferator‐activated receptor – delta activator GW501516 (2 mg/kg/day, 14 days) attenuated eNOS uncoupling and decreased superoxide anion production in cerebral microvessels of Tg2576 mice ( p  < 0.05). Treatment with GW501516 restored the biological activity of endothelial nitric oxide in cerebral microvessels of Tg2576 mice, as indicated by the increased nitrite/nitrate content and 3, 5‐cyclic guanosine monophosphate levels ( p  < 0.05). Our studies indicate that sub‐optimal BH4 bioavailability in cerebral vasculature is an important contributor to oxidant stress and endothelial dysfunction in Tg2576 mouse model of Alzheimer's disease. Existing evidence suggests that Aβ peptides‐induced up‐regulation of expression and activity of NADPH oxidase causes increased production of superoxide anion (.O2 − ). .O2 − can also be converted to hydrogen peroxide (H2 O2 ) by enzymatic activity of superoxide dismutase (SOD) or spontaneous dismutation. Elevation of .O2 − and H2 O2 might cause oxidation of tetrahydrobiopterin (BH4 ) to dihydrobiopterin (BH2 ) and subsequent uncoupling of endothelial nitric oxide synthase (eNOS) (a) thus reducing levels of nitric oxide (NO) and 3′, 5′‐cyclic guanosine monophosphate (cGMP). Supplementation of BH4 or activation of PPARδ prevents detrimental effects of eNOS uncoupling by restoring bioavailability of BH4 and scavenging of .O2 −, respectively (b). Activation of PPARδ also increases expression of catalase thereby inactivating H2 O2 . Generation of H2 O2 by uncoupled eNOS in cerebral microvessels of Tg2576 mice is hypothetical. Abstract : Existing evidence suggests that Aβ peptides‐induced up‐regulation of expression and activity of NADPH oxidase causes increased production of superoxide anion (.O2 − ). .O2 − can also be converted to hydrogen peroxide (H2 O2 ) by enzymatic activity of superoxide dismutase (SOD) or spontaneous dismutation. Elevation of .O2 − and H2 O2 might cause oxidation of tetrahydrobiopterin (BH4 ) to dihydrobiopterin (BH2 ) and subsequent uncoupling of endothelial nitric oxide synthase (eNOS) (a) thus reducing levels of nitric oxide (NO) and 3′, 5′‐cyclic guanosine monophosphate (cGMP). Supplementation of BH4 or activation of PPARδ prevents detrimental effects of eNOS uncoupling by restoring bioavailability of BH4 and scavenging of .O2 −, respectively (b). Activation of PPARδ also increases expression of catalase thereby inactivating H2 O2 . Generation of H2 O2 by uncoupled eNOS in cerebral microvessels of Tg2576 mice is hypothetical.